Environmental Effects Of Abattoir Operations In Gwagwalada Area Council, Federal Capital Territory, Abuja - Ekpo, C. G. (Advances in Social Sciences Research Journal, 2019)
This study investigated environmental problems associated with abattoir operations in Gwagwalada, FCT, Abuja. The study focused on human health and the physical environmental effects of the operations of the abattoir. The descriptive survey design was adopted for the study. Two hundred and fifty (250) respondents including staff, users, and residents around the abattoir were randomly selected for the study. Data for the study were collected through a close-ended questionnaire designed by the researcher, and constructed in a four-point Likert scale format. Descriptive statistics like frequency counts, mean (x) and simple percentage were used to analyze data collected with respect to research questions that were raised while the chi-square statistic was used to test the formulated hypotheses at 0.05 level of significance. The findings revealed that operations of Gwagwalada abattoir are not environmentally friendly, and that it poses serious health and environmental threats to the residents. Based on this, upgrading of the abattoir with modern infrastructures and facilities; tarring of the entire premises as well as construction of drainage and gutters; and sensitization of workers and residents of the abattoir on the environmental effects of improper management of abattoir wastes, among others, were recommended.